Suriname : 2011 Article IV Consultation-Staff Report, Informational Annex, Public Information Notice on the Executive Board Discussion and Statement by the Executive Director for Suriname. (IMF Staff Country Reports; Country Report, 2011)
In this paper, the economic growth of Suriname is discussed. The fiscal deficit shifted from 2.2 percent to 3.3 percent of GDP during 2009-10. In 2010, CLICO-Suriname was acquired by a local insurance company. The need to rein in current expenditure and avoid development of wage-price inflation and strengthen the social support programs are stressed by the authorities. The introduction of VAT and other systems are discussed. Finally, improvement over the business environment to facilitate the development of the private sector and global economy was encouraged.